The power of pupils in predicting conforming behavior. (3rd April 2019) - Brambilla, Marco; Biella, Marco; Kret, Mariska E.
ABSTRACT: During social interactions, people look into each other's eyes to grasp emotional signals. Accordingly, prior research has shown that the eyes reveal social messages that influence interpersonal communication. Here, we tested whether variations in a subtle eye signal – pupil size – influence people's conforming behavior. Participants performed an estimation task in light of the estimation provided by another individual whose pupil size had been manipulated. The distance between the two estimations was taken as an index of spontaneous conformity. Results revealed that participants conformed more strongly toward individuals with large pupils than toward individuals with small or medium pupils. These findings suggest that pupil size is a source of social influence that impacts upon spontaneous interpersonal conducts.